Targeting Cytochrome P450 Enzymes in Ovarian Cancers: New Approaches to Tumor-Selective Intervention - Yousef M. Al-saraireh; Fatemah O. F. O. Alshammari; Omar H. Abu-azzam; Sa’ed M. Al-dalain; Yahya M. Al-sarayra; Mansour Haddad; Hafiz Makeen; Aiman Al-Qtaitat; Mohammad Almermesh; Sameeh A. Al-sarayreh (Biomedicines, 2023)
Over the past decade, there have been significant developments in treatment for ovarian cancer, yet the lack of targeted therapy with few side effects still represents a major issue. The cytochrome P450 (CYP) enzyme family plays a vital role in the tumorigenesis process and metabolism of drugs and has a negative impact on therapy outcomes. Gaining more insight into CYP expression is crucial to understanding the pathophysiology of ovarian cancer since many isoforms are essential to the metabolism of xenobiotics and steroid hormones, which drive the disease’s development. To the best of our knowledge, no review articles have documented the intratumoral expression of CYPs and their implications in ovarian cancer. Therefore, the purpose of this review is to provide a clear understanding of differential CYP expression in ovarian cancer and its implications for the prognosis of ovarian cancer patients, together with the effects of CYP polymorphisms on chemotherapy metabolism. Finally, we discuss opportunities to exploit metabolic CYP expression for the development of novel therapeutic methods to treat ovarian cancer.